Stillness, breath and the spine - Dance performance enhancement catalysed by the interplay between 3D motion capture technology in a collaborative improvisational choreographic process - Nikolai, J.; Bennett, G. (Performance Enhancement & Health, 2015)
We propose that Motion Capture (MoCap) in dance is part of, but distinct from, the traditional use of film or video as an archival and indexical instrument. Furthermore in the move from the recording of framed and temporally consistent slices of linear film or video `footage` to the collection of profoundly mutable digital data utilising an Omniscient Frame, there is a fundamental conceptual shift in the creative re-shaping of the performance through a shared choreographic process. In the improvised choreographic and live performance process, qualitative differences in evaluating MoCap were identified. Study #1 (2015) is a collaborative screendance work by the authors, dancer (Author One), and digital artist (Author two). This piece utilises 3D Motion Capture technology and 3D digital animation software as part of a series of dance and moving image experiments. MoCap offers enhanced perspectives towards compositional awareness and evaluation between live and digital platforms. The human movement material produced in response to the MoCap technology optimises the potential of the technology and the human, moving body, with a catalysing force. We propose that what is transferred from live to digital via the omniscient motion capture camera informs what we see towards creative possibilities. We identify that the live performer as movement data does manifest as digital presence. We propose that we can view dance data and that this does aid performance - not towards quantitative evaluation but in capturing specific, human movement qualities towards qualitative artistic evaluation and critique.